Age group development and competition program for women`s artistic gymnastics - Fink, H.; Hofmann, D.; Ortez Lopez, L. (2015)
Overview and Philosophy of FIG Age Group Development Program Overview of Long Term Gymnast Development Competition Program - Compulsory Exercises and Optional Rules Compulsory Exercises Physical and Technical Ability Testing Program Skill Acquisition Profiles